Discovering the music of Japan [videorecording] - Wilets, Bernard (Encyclopedia Britannica Educational Corporation [producer], 1982)
Introduces the traditional music of Japan. Discusses the origins of Japan's three major instruments, the Koto, the Shamisen and the bamboo flute called shakuhachi. The music of ancient as well as modern composers reflects the Japanese people's love of nature.